Escherichia coli from biopsies differ in virulence genes between patients with colorectal neoplasia and healthy controls - Bosák, Juraj; Kohoutová, Darina; Hrala, Matěj; Křenová, Jitka; Morávková, Paula; Rejchrt, Stanislav; Bureš, Jan; Šmajs, David (Frontiers in microbiology, 2023)
INTRODUCTION: Pathogenic strains of Escherichia coli have been clearly identified as the causative agents of extraintestinal and diarrheal infections; however, the etiopathogenic role of E. coli in other conditions, including colorectal cancer, remains unclear. METHODS: This study aimed to characterize mucosal E. coli isolates (n = 246) from 61 neoplasia patients and 20 healthy controls for the presence of 35 genetic determinants encoding known virulence factors. RESULTS: Virulence determinants encoding invasin (ibeA), siderophore receptor (iroN), S-fimbriae (sfa), and genotoxin (usp) were more prevalent among E. coli isolated from patients with neoplasia compared to the control group (p < 0.05). In addition, the prevalence of these virulence determinants was increased in more advanced neoplasia stages (padj < 0.0125). Compared to patients with advanced colorectal adenoma and carcinoma, the ibeA gene was rarely found in the control group and among patients with non-advanced adenoma (p < 0.05), indicating its potential as the advanced-neoplasia biomarker. Patients with neoplasia frequently had E. coli strains with at least one of the abovementioned virulence factors, whereby specific combinations of these virulence factors were found. DISCUSSION: These findings suggest that E. coli strains isolated from patients with colorectal neoplasia possess several virulence factors, which could contribute to the development of neoplastic processes in the large intestine.